Balloon dilation of the eustachian tube using endovascular balloon under local anesthesia—a case series and systematic literature review - Ungar, Omer J.; Demir Bajin, Münir; Dahm, Valerie; Lin, Vincent Y. W.; Chen, Joseph M.; Le, Trung N. (Frontiers in Surgery, 2024)
Objective To report a novel technique in Balloon Dilation of Eustachian Tube (BDET) using an endovascular balloon (EVB), in a prospective cohort. The results are compared with reported outcomes using standard balloons. Methods Demographic information and clinical parameters were collected prospectively fora series of patients with obstructive eustachian tube dysfunction (OETD). Balloon dilation Eustachian tuboplasty was performed under local anesthesia in a tertiary referral center, using the EVB. Systematic literature review was used for comparison, using Medline via “PubMed”, “Embase”, and “Web of Science”. Results Eight OETD candidates (12 ears) were enrolled; 5 males and 3 females. Average age was 48 (range −23 to 63) years. The most common presenting symptom was aural fullness (9/12), followed by ear pressure (7/12), hearing loss (5/12) and tinnitus (4/12). Otoscopically, tympanic membrane retraction was evident in 10/12 ears, the majority of which was class II—Sade classification. Pre-operative tympanogram was type B and C in 7 and 5 ears, respectively. All BDETs were performed without complications. Post-operative tympanometry was A in 8/12 ears. Post-operatively, Eustachian Tube Dysfunction Questionnaire-7 results reduced to within normal limits (average score ≤3) in 11/12 ears (p = 0.0014). The systematic literature review included 6 papers (193 patients, 262 ETs) with comparable results, most also with little adverse effects. Conclusion BDET using an EVB is a safe and effective option for OETD. It is well tolerated under local anesthesia in properly selected individuals. The reduced procedural cost may be an important factor in certain healthcare jurisdictions.